Determine the Relationship Between Abdominal Muscle Strength, Trunk Control and Urinary Incontinence in Children with Diplegic Cerebral Palsy - Talu, Burcu (Urology Journal, 2018)
Purpose: The aim of this study is to determine the relationship between abdominal muscle strength, trunk control and urinary incontinence in children with diplegic cerebral palsy. Materials and methods: The current study had a cross-sectional design using analytical study as well as an observational research model. Fifty children between the ages of 5 and 18 years who were diagnosed with diplegic clinical type of cerebral palsy were included in this study using improbable-random sampling method. After patients' demographic information were obtained, Dysfunctional Voiding and Incontinence Symptoms Score Questionnaire (DVISS), Dysfunctional Voiding Symptom Score (DVSS), the manual muscle test of the muscles, Trunk Control Test (TCT) and Trunk Control Measurement Scale (TCMS) were completed in order to evaluate trunk control. Also, Gross Motor Function Classification System (GMFCS) was performed in order to define the functional level. Results: In this study, a highly correlated negative relationship was found between DVISS and DVSS scores with muscle abdominal strength, TCMS and TCT. In addition, a highly correlated positive relationship was found between both GMFCS and DVISS and GMFCS and DVSS. Conclusion: This is the first study that describes the effect of trunk control and muscle strength on urinary incontinence in children with diplegic cerebral palsy. This study showed that there is a correlation between trunk control, muscle strength and urinary incontinence.